Strand invasion promoted by recombination protein β of coliphage λ - Rybalchenko, Nataliya (National Academy of Sciences, 2004)
Studies of phage λ in vivo have indicated that its own recombination enzymes, β protein and λ exonuclease, are capable of catalyzing two dissimilar pathways of homologous recombination that are widely distributed in nature: single-strand annealing and strand invasion. The former is an enzymatic splicing of overlapping ends of broken homologous DNA molecules, whereas the latter is characterized by the formation of a three-stranded synaptic intermediate and subsequent strand exchange. Previous studies in vitro have shown that β protein has annealing activity, and that λ exonuclease, acting on branched substrates, can produce a perfect splice that requires only ligation for completion. The present study shows that β protein can initiate strand invasion in vitro, as evidenced both by the formation of displacement loops (D-loops) in superhelical DNA and by strand exchange between colinear single-stranded and double-stranded molecules. Thus, β protein can catalyze steps that are central to both strand annealing and strand invasion pathways of recombination. These observations add β protein to a set of diverse proteins that appear to promote recognition of homology by a unitary mechanism governed by the intrinsic dynamic properties of base pairs in DNA.